2021
DOI: 10.1002/cbdv.202000936
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect ofNigella sativaandNigella damascenaFixed Oils Against Aflatoxin Induced Mutagenicity in the Classical and Modified Ames Test

Abstract: The antioxidant and mutagenic/antimutagenic activities of the fixed oils from Nigella sativa (NSO) and Nigella damascena (NDO) seeds, obtained by cold press‐extraction from the cultivar samples, were comparatively investigated for the first time. The antimutagenicity test was carried out using classical and modified Ames tests. The fatty acid composition of the fixed oils was characterized by gas chromatography–mass spectrometry (GC‐MS) while the quantification of thymoquinone in the fixed oils was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The genus Nigella includes about 22 species of annual herbs belonging to the buttercup family (Ranunculaceae) [ 1 ]. The term Nigella comes from the Latin “ niger ”, a reference to the intense black color of seeds in most Nigella species; the best known of these species are Nigella sativa L. (NS) and Nigella damascena L. (ND) [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Nigella includes about 22 species of annual herbs belonging to the buttercup family (Ranunculaceae) [ 1 ]. The term Nigella comes from the Latin “ niger ”, a reference to the intense black color of seeds in most Nigella species; the best known of these species are Nigella sativa L. (NS) and Nigella damascena L. (ND) [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nigella sativa L. is commonly known as black cumin, black seed, habba Saouda and senoudj or sinoudj in Algeria and the Maghreb countries. It is naturally grown in North Africa, southern Europe, the Middle East, and Southwest Asia, and is widely cultivated for numerous industrial and medicinal purposes (food and therapeutic uses) [ 1 , 5 , 6 , 7 ] mainly in India, Pakistan, Iran, Syria, Turkey, Ethiopia, Oman, and Saudi Arabia [ 8 , 9 , 10 ]. The NS seeds stimulate great interest in the food, cosmetics, and pharmaceutical fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aflatoxin B1‐induced mutagenicity was examined in N. damascena seed oil using S. typhimurium strains. The study found no influence on bacterial viability and no evidence of cytotoxicity in the tested strains at a 5000 μg concentration per plate [59] …”
Section: Bioactivities Of Some Nigella Sppmentioning
confidence: 70%
“…The study found no influence on bacterial viability and no evidence of cytotoxicity in the tested strains at a 5000 μg concentration per plate. [59]…”
Section: Anticancer Activitymentioning
confidence: 99%